THE IMPACT OF SERVICE QUALITY AND TRUST ON CUSTOMER SATISFACTION - Muhamad Junaidi; Achmad Daengs GS; Rina Dewi; Enny Istanti; Ruchan Sanusi (PT. Mawadaku Sukses Solusindo, 2023)
Nowadays business competition cannot be avoided, whether in the form of products or services, so the business always has its strategy to win. In this condition, service is the most important factor that must be built and provided to customers. Therefore, service must be quality. With quality service, customers will also be satisfied and then they will not leave the company. Quality service is characterized by the number of consumers who are satisfied with the service. PT. TIKI Pakis Surabaya Branch is the object of research because service quality is very important. Theoretically, there are five dimensions of service quality such as tangibles, reliability, responsiveness, assurance, and empathy which can influence customer satisfaction. This research aims to determine the effect of service quality on customer satisfaction. Structural equation modeling (SEM) is used to analyze primary and secondary data. With a probability level of ≥ 0.10, it was found that the assurance dimension can build unidimensionality of service quality, while the tangibles, reliability, responsiveness, and empathy dimensions cannot. Therefore, it can be concluded that quality assurance is the dominant factor that causes customer satisfaction.